The Relationship Between The Implementation of Patient Safety and The Quality of Nursing Services at Purwokerto Islamic Hospital - Yolanda Natasha; Etlidawati Etlidawati (Proceedings Series on Health & Medical Sciences, 2024)
Background : Patient safety in drug administration is still a top global health priority because patient safety has become the most important indicator in the health care system for good and bad patient health. The lower the implementation of patient safety in administering medication, the better the quality of nursing services will be. Research Objective: To determine the relationship between the implementation of patient safety in administering inpatient medication and the quality of nursing services at RSI Purwokerto. Method: Quantitative methods were used with a correlational descriptive design with a cross-sectional approach. The sampling technique was total sampling, totaling 90 respondents. Results: From this research, the results showed that there were 41 inpatient nurses (91.1%) who implemented patient safety in administering medication well, and 42 inpatient nurses (93.3%) who assessed the quality of nursing services at RSI Purwokerto as good . The results of the bivariate analysis showed that there was a significant relationship between the implementation of patient safety in administering medication and the quality of nursing services at RSI Purwokerto (p0.05). Conclusion: There is a relationship between the implementation of patient safety in inpatient medication administration and the quality of nursing services in hospitals.